1989 in South(ern) Africa: The Fall of the Nuclear Wall - van Wyk, Anna-Mart; Möser, Robin (Comparativ, 2019)
Resting on newly obtained archival sources and interviews with key actors, this article aims at filling some gaps in the historiography on the end of the Cold War in Southern Africa. It discusses the final years of the South African nuclear weapons programme against the backdrop of the winding down of the Global Cold War in the Southern African region. It argues that the events in Eastern Europe in 1989 should be juxtaposed against the fundamental changes in South Africa after a decades-long liberation struggle against the oppressive Apartheid regime. It shows how September 1989 proved to be as significant in South Africa as it was in Leipzig.F.W. de Klerk’s election as State President put South Africa on a path of unprecedented reform, including a decision to tear down Apartheid’s proverbial ‘nuclear wall’. The paper argues that while the decision of the De Klerk government to terminate and dismantle the indigenously developed nuclear weapons arsenal was triggered by a confluence of domestic and regional factors, the events in Eastern Europe also had an influence, not least being the impending fall of the Soviet Union, the Apartheid’s regime decades-long enemy. The decision to denuclearize furthermore had important repercussions beyond the region. This is exemplified by the phoenix-like rise of Pretoria’s leaders on the global non-proliferation scene, following the end of its programme and NPT accession.